The antagonist and protagonist approaches of televising extremism and terrorism - El Zein, Hatem (Penerbit Universiti Kebangsaan Malaysia, 2017)
This paper illuminates a current issue related to reporting extremism and terrorism because the developments in the communication technology and the spawn of television stations that seek scoop have allowed the extremists and terrorists not only to transmit their messages, but also to recruit followers and entice supporters throughout the world. Owing to this emerged problem, this paper answers the following question: can the mainstream media televise extremism and terrorism and what is the suitable approach in this regard? To approach this question, this paper reviews the existing literature and debate related to reporting extremism and terrorism. Guided by agenda-setting theory, it adopts a qualitative approach and focuses in the analysis on two contemporary cases aired by Australian broadcasters to verify the argument that the media should be professional and responsible in the cases related to reporting extremism and terrorism. This paper concludes that the media may maximize the publicity of the extremists and terrorists and consequently it may allow them to achieve their agendas. Drawing on these findings, this paper develops models related to the significance of media to the extremists and terrorists and their targeted audiences. Thus, it presents a set of recommendations can be adopted by the media outlets when they report extremism and terrorism.